Impact of Import Duties and PPh 22 Rates on Electronics and Telematics Industry Production Performance - Adam, Muhammad Ibrahim; Faturohman, Taufik (Granada El-Fath, 2024)
In this study, the authors attempt to provide an analysis of the effects of import duty rates and PPh22 rates on the performance of the electronics and telecommunications industry in Indonesia by considering the years 2022 and 2023 as the main data. The study also aims to understand through statistical methods the effects of these fiscal policies on various parameters of industry performance with special reference to local production. The study shows that while the policy may strengthen domestic production, there are considerable challenges in the export growth sector. In addition, the greater fiscal burden makes Indonesian electronics and telecommunications products less competitive at the international market level. Meanwhile, direct export tariffs have arguably the least effect on exports compared to PPh22, but the combination of these two policies will affect raw material costs in aggregate, which in turn negatively affects the competitiveness of export products. This study underscores the importance for policymakers in balancing between the export tariff of PPh22 and other types of tariff acceleration for levying considerations for domestic production levels and binding competitiveness. Therefore, optimizing the management of this fiscal policy is deemed very necessary to be examined in order to boost sustainable growth for the electronics and telecommunications industry in Indonesia and the addition of local production capacity.